Livestock intensification and smallholders: a rapid reconnaissance of the Philippines hog and poultry sectors - Rola, Agnes; Rola, Walfredo; Tiongco, Marites; Delgado, Christopher L. (International Food Policy Research Institute, 2003)
This essay describes the views of Philippines livestock sector stakeholders concerning the events and issues associated with the rapid rise in hog and poultry production, based on rapid reconnaissance interviews and gray literature from studies in Southern Luzon, Iloilo and Northern Mindanao, and the impressions of the authors. Changing demographic patterns, decentralized eco-governance, trade liberalization, and health and environmental policies have major impacts on further livestock intensification and on increasing scale of operations. Six factors appear to affect small farmers' decisions to intensify or raise livestock, or remain in the livestock industry. These are 1) access to financial capital; 2) technical knowledge about livestock production and their sources of information; 3) social capital expressed as trust in integrators, in the primary buyers of the livestock, and in government; 4) demographic characteristics, such as gender and age; 5) farmer perceptions of the policy environment (prices, feeds, health and environmental policies, and the local ordinances affecting the livestock sector); and 6) access to reliable markets for outputs across the year. -- Authors' Abstract